Creative Thinking Dispositions of Truth-Seeking Students in Solving Higher-Order Thinking Skills Questions - Prastya, Iwan; Wyrasti, Andi Fajeriani; Irnandi, Irfan (Universitas Muhammadiyah Mataram, 2023)
This study intended to investigate the creative thinking dispositions of students who can perform truth-seeking in solving mathematical problems. Truth-seeking behavior tends to show students' thinking disposition when they need to solve math problems. This behavior is very much needed by students in solving math problems, especially HOTS-type questions. This study is qualitative and employs a phenomenological approach. Three students from the Integrated Islamic Junior High School in Manokwari who sought the truth served as research subjects. Their answers on the answer sheets encouraged the determination of the subjects’ tendencies in truth-seeking and creative thinking. The results of thought-based and task-based interviews were then incorporated into the analysis to determine the creative thinking dispositions of truth-seeking students and the relationship between truth-seeking and creative thinking dispositions. The findings of this study indicate that all research subjects have diverse creative thinking dispositions; the more truth-seeker indicators that are met, the more creative thinking dispositions they possess. When solving mathematical problems, students tend to show how they think by how hard they try to find the truth. This result implies that it needs more research on the level of creative thinking disposition and how to increase students' true search.